Potential sources of interference with the highly sensitive detection and quantification of alpha‐synuclein seeds by qRT‐QuIC. Issue 5 (10th April 2020) - Ruf, Viktoria C.; Shi, Song; Schmidt, Felix; Weckbecker, Daniel; Nübling, Georg S.; Ködel, Uwe; Mollenhauer, Brit; Giese, Armin
Abstract : Parkinson's disease (PD) is a progressive neurodegenerative disease which is histologically characterized by loss of dopaminergic neurons in the substantia nigra and deposition of aggregated alpha‐synuclein (aSyn) in the brain. The detection of aSyn in well accessible fluids has been one of the central approaches in the development of biomarkers for PD. Recently, real‐time quaking‐induced conversion (RT‐QuIC) has been successfully adapted for use with aSyn seeds. Here, we systematically analysed parameters potentially impacting the reliability of this assay by using quantitative real‐time quaking‐induced conversion (qRT‐QuIC) with in vitro ‐formed aSyn seeds. Seeds diluted in cerebrospinal fluid (CSF) accelerated the seeding reaction and slightly increased the sensitivity without affecting specificity. Repeated freeze–thaw cycles decreased the apparent lag times of seeds diluted in ddH2 O but did not alter the seeding activity of seeds diluted in CSF. High levels of artificial contamination with blood resulted in prolonged apparent lag times, while sensitivity and specificity were unaffected. Altogether, qRT‐QuIC with aSyn seems to be robust concerning sensitivity and specificity in our model system, but quantitative interpretation might be limited under certain conditions. Abstract : RT‐QuIC with alpha‐synuclein represents a promising tool for the early diagnosis of synucleinopathies from cerebrospinal fluid. We tested typical conditions like repeated freeze–thaw cycles or contamination with blood which may impair the functionality of the assay. While freeze–thaw cycles do not seem to have a major impact, blood prolonged the apparent lag phases but did not change sensitivity or specificity of the assay.